Dietary factors and patterns in relation to risk of later-onset ulcerative colitis in Chinese: a prospective study of 0.5 million people - Song, S; Wu, Z; Lv, J; Yu, C; Sun, D; Pei, P; Pan, L; Yang, L; Chen, Y; Du, H; Chen, L; Schmidt, D; et al. (Wiley, 2024)
Background: There is limited evidence on the associations of dietary factors and patterns with risk of later-onset ulcerative colitis (UC) in Chinese adults.